Self-repairing antirust lubricating aerosol and preparation method thereof

By adding petroleum resin, graphite, metal bismuth powder and low molecular weight polytetrafluoroethylene powder to the anti-rust lubricating aerosol, the problems of poor film formation effect and insufficient self-repair ability are solved, and high efficiency is achieved Anti-rust, lubrication and self-repairing effects.

CN119505979APending Publication Date: 2025-02-25ZHEJIANG LUDAO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411653299.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing anti-rust lubricating aerosol has poor film formation effect after spraying, and it cannot effectively repair metal friction surface defects.

Method used

By enhancing the permeability and film spreading properties of the lubricant, a self-healing film is formed by using components such as petroleum resin, graphite, metal bismuth powder and low molecular weight polytetrafluoroethylene powder to form a self-healing film to ensure that the aerosol can effectively adhere and Repair metal surfaces.

Benefits of technology

It realizes the uniform film formation and self-healing functions of aerosol on the metal surface, enhances the anti-rust, lubrication and cleaning effects, and is suitable for various metal parts of complex shapes and operating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505979A_ABST
    Figure CN119505979A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anti-rust lubricants, and particularly relates to a self-repairing anti-rust lubricating aerosol and a preparation method thereof. The anti-rust lubricant is characterized by comprising an anti-rust lubricant and a propellant, the anti-rust lubricant is prepared from the following raw material components in percentage by mass: 18 to 20 percent of base oil, 5 to 8 percent of an anti-rust agent, 4 to 6 percent of auxiliary lubricating oil, 3 to 5 percent of a penetrating agent, 4 to 6 percent of dibutyl ether, 1 to 1.5 percent of petroleum resin, 0.5 to 1 percent of low-molecular-weight polytetrafluoroethylene micro powder, 0.5 to 0.8 percent of graphite, 0.3 to 0.5 percent of metal bismuth powder, 0.2 to 0.3 percent of stearic acid, 0.1 to 0.2 percent of sorbitan monooleate and the balance of water. And the balance of hydrogenated deodorized kerosene. And the use amount of the propellant is 40-45% of the total mass of the antirust lubricant. Through synergistic raw material combination, the lubricating oil has relatively low surface tension, is easy to disperse, permeate and spread, and is attached to a friction surface to form a film; through the cooperation of the graphite, the metal bismuth powder and the low-molecular-weight polytetrafluoroethylene micro-powder, the metal bismuth powder can be fixed on a metal surface and defects or tiny cracks on the metal surface, and micro defects on a friction interface are dynamically repaired.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rust-proof lubricants, and in particular relates to a self-repairing rust-proof lubricating aerosol and a preparation method thereof. Background Art

[0002] With the rapid development of precision machinery, the requirements for anti-corrosion, lubrication and wear resistance of various metal parts, accessories, bearings, screws, molds, etc. during use and storage are getting higher and higher. For example, the precision molds used in plastic injection molding will produce volatile gases after heating. These gases are mostly corrosive and will corrode the mold mirror surface; when the mold is stored, the surface of the mold is easily corroded and rust spots are formed due to the high humidity of the storage environment or poor ventilation. For another example, the operation, assembly, disassembly and storage of workpieces such as bearings all require anti-rust lubrication treatment.

[0003] Currently, anti-rust lubricants have been used in many scenarios such as mold protection, machinery protection, weapon protection, screw disassembly and assembly, precision parts disassembly protection, and rusted parts disassembly.

[0004] Conventional anti-rust lubricants are generally grease or high-viscosity lubricating pastes. On the one hand, it is inconvenient to apply. On the other hand, it is difficult to apply to special-shaped parts or running metal parts, and it is difficult for lubricating oil to penetrate the micropores of metal. The anti-rust lubricant is made into an aerosol. The aerosol carries the lubricating oil through solvents and propellants. The lubricating oil can be easily transported and applied to the surface of complex-shaped mechanical parts, mechanical micropores, etc., and the lubricating oil can be applied without stopping or disassembling the machine. Compared with the traditional paste lubrication method, it saves more lubricating oil and forms a more uniform oil film. At present, anti-rust lubricating aerosols have been widely used in various industrial equipment, aircraft, automobiles, etc. Especially in harsh environments such as high speed, high temperature, and operation, aerosol lubrication can better protect machinery and equipment, extend service life, and keep the friction interface clean.

[0005] However, aerosol lubricants contain more solvents or diluents and dispersants, which results in high fluidity after spraying. The oil film dispersed on the metal surface is difficult to fix into a film due to the low viscosity of the lubricant. Compared with grease or high-viscosity lubricating oil, the oil film of aerosol lubricants is thin and has limited protective effect. In addition, lubricants are mostly used to repair metal friction surfaces by adding the repair agent to a paste or high-viscosity lubricant, and relying on dynamic friction to stably fill the repair agent on the damaged interface. Aerosol lubricants are highly fluid, and the repair agent directly used in aerosols cannot effectively form a film to fix and repair defects on the metal friction surface. Summary of the invention

[0006] In view of the technical problems that the current anti-rust lubricating aerosol has poor film-forming effect after spraying and cannot effectively self-repair defects on metal friction surfaces, the present invention proposes a self-repairing anti-rust lubricating aerosol. By enhancing the permeability and spreading film-forming property of the lubricant, it is easy to disperse, penetrate, spread, and adhere to the friction surface to form a film when used, and has good cleaning, rust prevention, and lubrication functions; and petroleum resin, graphite, metal bismuth powder, and polytetrafluoroethylene powder are dissolved and dispersed in dibutyl ether, and the volatilization of dibutyl ether after spraying is utilized to allow the petroleum resin to adhere to form a film, thereby forming a self-repairing film; further, a preparation method of the self-repairing anti-rust lubricating aerosol is provided.

[0007] In order to achieve the above technical objectives, the present invention provides the following specific technical solutions:

[0008] First, the present invention provides a self-repairing anti-rust lubricating aerosol, which is characterized by comprising an anti-rust lubricant and a propellant; wherein:

[0009] The anti-rust lubricant comprises the following raw material components by mass percentage: 18-20% base oil, 5-8% anti-rust agent, 4-6% auxiliary lubricating oil, 3-5% penetrant, 4-6% dibutyl ether, 1-1.5% petroleum resin, 0.5-1% low molecular weight polytetrafluoroethylene powder, 0.5-0.8% graphite, 0.3-0.5% metal bismuth powder, 0.2-0.3% stearic acid, 0.1-0.2% sorbitan monooleate, and the rest is hydrogenated deodorized kerosene;

[0010] The amount of the propellant is 40-45% of the total mass of the anti-rust lubricant;

[0011] The base oil is a mixture of perfluoropolyether oil, mineral oil and silicone oil in a mass ratio of 3-5:2:1;

[0012] The rust inhibitor is at least one of barium petroleum sulfonate, calcium petroleum sulfonate, sodium petroleum sulfonate, barium dinonylnaphthalene sulfonate, calcium dinonylnaphthalene sulfonate, 2,6-di-tert-butyl-p-cresol (BHT), and dodecenylsuccinic acid;

[0013] The auxiliary lubricating oil is one of tung oil, sulphurized cottonseed oil and butyl oleate;

[0014] The penetrant is prepared by mixing tetrafluoropropanol and tridecafluoroheptanoic acid in a mass ratio of 1-2:1;

[0015] The petroleum resin is at least one of C5 aliphatic petroleum resin, C9 aromatic petroleum resin, C5-C9 aliphatic / aromatic copolymer petroleum resin, and alicyclic petroleum resin;

[0016] The propellant is a complex of at least one of liquefied petroleum gas (LPG), dimethyl ether (DME), carbon dioxide (CO2) and nitrogen.

[0017] Further preferably, the base oil is a mixture of perfluoropolyether oil, mineral oil and silicone oil in a mass ratio of 4:2:1; perfluoropolyether oil is non-flammable, stable to highly corrosive acids and alkalis under high temperature conditions, has low surface tension, low volatility, good viscosity and is easy to form a film. By combining mineral oil and silicone oil to form a base oil, it has good dispersibility, spreadability and wet film-forming properties at the metal interface, and is easier to form a micro oil film.

[0018] Further preferably, the rust inhibitor is dodecenylsuccinic acid; it is easy to disperse in an aerosol, and when used, it can form a firm, uniform and delicate oil film on the metal surface, preventing the penetration of corrosive substances and fully protecting the metal from rust.

[0019] Further preferably, the auxiliary lubricating oil is sulphurized cottonseed oil; it has good extreme pressure and anti-wear properties and good adhesion.

[0020] Further preferably, the penetrant is a mixture of tetrafluoropropanol and tridecafluoroheptanoic acid in a mass ratio of 1:1; tetrafluoropropanol has good surface activity and solubility and permeability, can penetrate and clean metal parts, can penetrate into the metal surface and micropores, dissolve rust, and facilitate the disassembly and cleaning of rusted screws and screws; tridecafluoroheptanoic acid has low surface tension, chemical stability and lubricity, and improves the wettability and adhesion of the aerosol to the metal surface; in typical applications, the penetrant is used in an aerosol, which can quickly penetrate the screw of a screw extruder, promptly remove the resin in the gap between the thread blocks, and facilitate the disassembly of the screw; it can clean rust spots or impurity spots adhered to the mirror surface of the injection mold.

[0021] Further preferably, the low molecular weight polytetrafluoroethylene micropowder is a low molecular weight polytetrafluoroethylene micropowder with a number average molecular weight (Mn) of 10,000-30,000 and a D50 particle size of less than 5 μm; it has excellent friction reduction and wear resistance and excellent chemical corrosion resistance; at the same time, the oil film formed by the low molecular weight polytetrafluoroethylene micropowder after spraying in an aerosol has good self-cleaning property and does not stick to dust, ensuring long-term lubrication of the metal surface.

[0022] Further preferably, the graphite flake graphite has a particle size of less than 5 μm; the graphite has a layered structure, the layers are easy to slide, and it has self-lubricating properties. It is lubricating, wear-resistant and stable under high speed, high temperature and high pressure conditions, and can well repair defects in the friction interface.

[0023] Further preferably, the metal bismuth powder is a bismuth powder with a particle size of less than 2 μm; during the friction process, it forms a self-lubricating and self-repairing film on the friction surface, significantly improving the lubrication and repair performance.

[0024] Further preferably, the propellant is a complex of at least one of liquefied petroleum gas (LPG), dimethyl ether (DME), carbon dioxide (CO2) and nitrogen in a mass ratio of 3-5:1; by auxiliary nitrogen, the lubricating oil in the aerosol can be effectively prevented from being oxidized, thereby extending the shelf life of the product, and the supplementary nitrogen can balance the pressure of the aerosol can.

[0025] Furthermore, a method for preparing the self-repairing anti-rust lubricating aerosol is provided, and the specific preparation method is as follows:

[0026] S1. According to the mass percentage, graphite, low molecular weight polytetrafluoroethylene powder, metal bismuth powder, and stearic acid are pre-compounded by mechanical grinding and dispersion, and then added to a ball mill with dibutyl ether, petroleum resin, and sorbitan monooleate, and closed grinding, dissolving, and dispersing under ceramic grinding ball conditions to obtain a slurry;

[0027] S2 according to the mass percentage ratio of the base oil, rust inhibitor, auxiliary lubricant, penetrant, hydrodeodorized kerosene added to the stirred tank and stirred evenly, then added S1 grinded slurry, stirred at low speed, filtered to obtain a rust-proof lubricant;

[0028] S3. The anti-rust lubricant obtained in step S2 is canned at normal pressure using a tinplate can as a container, the valve is sealed, a propellant is charged, the weighing test and the water bath test are performed, and a nozzle is installed to obtain a self-repairing anti-rust lubricating aerosol.

[0029] Further preferably, the ball mill described in step S1, the speed is controlled at a low speed of 15-25rpm, grinding for 20-30min, pay attention to the closed operation of the ball mill to prevent volatilization and fire source; the particle size of the ceramic grinding ball is 3mm. By grinding and dispersing, the petroleum resin is dissolved in dibutyl ether, and graphite, metal bismuth powder, and low molecular weight polytetrafluoroethylene powder are pre-dispersed; petroleum resin has excellent adhesion, which is dissolved in dibutyl ether for aerosol. After spraying, it can enhance the adhesion of the lubricant, and with the rapid volatilization of dibutyl ether, the lubricant is firmly attached to the friction surface, thereby improving the lubrication effect. At the same time, graphite, metal bismuth powder, and low molecular weight polytetrafluoroethylene powder are fixed on the metal surface and the defects or tiny cracks on the metal surface to form a self-repairing interface, so as to achieve the lubrication and repair functions of the lubricant.

[0030] Further preferably, the graphite, low molecular weight polytetrafluoroethylene powder, metal bismuth powder and stearic acid in step S1 are pre-compounded by mechanical grinding and crushing dispersion; the mechanical grinding and crushing can adopt methods including but not limited to: air flow crushing, pin grinding and crushing, vortex air flow crushing, impact grinding and crushing; graphite, metal bismuth powder and low molecular weight polytetrafluoroethylene powder work together to have good lubricity and self-repairing properties. In typical applications, when used on metal surfaces with rust pits, graphite, metal bismuth powder and low molecular weight polytetrafluoroethylene powder are deposited and fixed on the pits due to the adhesion of petroleum resin. When the metal parts are lubricated during operation, they are subjected to friction and extrusion, and the graphite, metal bismuth powder and low molecular weight polytetrafluoroethylene powder will stably fill the pits or microcracks, thereby achieving the purpose of self-repair and lubrication of the metal parts.

[0031] The present invention discloses a self-repairing anti-rust lubricating aerosol and a preparation method. The aerosol can be used to clean metal parts by using a penetrant, and can penetrate into the metal surface and micropores to dissolve rusted materials, which is beneficial to the disassembly and cleaning of rusted screws and screws. The aerosol has a low surface tension and can form a uniform microfilm on the metal surface to prevent the metal parts from contacting with air, water, acid and alkali liquids, thereby preventing the metal parts from rusting. By using petroleum resin, the adhesion of the aerosol can fix graphite, metal bismuth powder, and low molecular weight polytetrafluoroethylene powder on the metal surface and defects or tiny cracks on the metal surface to form a self-repairing interface to achieve lubrication and repair functions. The canned aerosol is stored in a dry and cool place, away from fire sources, heat sources, power sources and other places.

[0032] The excellent effects of the present invention are embodied in:

[0033] 1. The present invention has a lower surface tension through a synergistic combination of raw materials, can form a uniform microfilm on the metal surface, enhances the permeability and spreading film-forming properties of the lubricant, and makes it easy to disperse, penetrate, spread, and adhere to the friction surface to form a film when used, and has good cleaning, rust prevention, and lubrication functions.

[0034] 2. The present invention uses petroleum resin to enhance the adhesion and film-forming property of the aerosol after spraying, thus overcoming the defect that the current lubricant aerosol is difficult to fix and form a film;

[0035] 3. The present invention can be fixed on the metal surface and the defects or tiny cracks on the metal surface by using the synergy of graphite, metal bismuth powder and low molecular weight polytetrafluoroethylene powder, and can well repair the micro defects of the friction interface.

[0036] 4. The aerosol of the present invention has a wide range of applications and strong practicality. It can penetrate rusty screws, molds, pistons, bearings, etc., remove surface rust and dirt, and form a protective lubricating and anti-rust oil film. Compared with liquid and paste lubricating oils, aerosols are convenient and efficient to use. They can be sprayed when metal parts are working and can be used on special-shaped parts. When tiny cracks appear on the metal friction surface, they can efficiently penetrate tiny cracks to repair the interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to further clarify the technical effects of the present invention, the present invention is further described below in conjunction with the accompanying drawings:

[0038] Figure 1 Example 1, Comparative Examples 5-7, a total of four groups of aerosol sprays were applied to the same batch of corroded rolling bearings. After spraying, the bearings were operated for 60 minutes under the same load, and the friction surface of the outer ring of the bearings was detected using a microscope, where:

[0039] A1 is a microscopic magnified image of the aerosol sprayed in Example 1;

[0040] A2 is a microscopic magnified image of the aerosol sprayed in Comparative Example 5;

[0041] A3 is a microscopic magnified image of the aerosol sprayed in Comparative Example 6;

[0042] A4 is a microscopic magnified image of the aerosol sprayed in Comparative Example 7. DETAILED DESCRIPTION

[0043] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the technical ideas of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0044] Basic raw material selection:

[0045] Low molecular weight polytetrafluoroethylene powder: low molecular weight polytetrafluoroethylene powder with a D50 particle size of less than 5μm provided by Quzhou Baimao Technology Co., Ltd.

[0046] Graphite: Flake graphite with a diameter less than 5μm produced in Qingdao;

[0047] Metal bismuth powder: bismuth powder with a particle size less than 2 μm.

[0048] Example 1

[0049] S1. According to the mass percentage, 0.5% of graphite, 0.5% of low molecular weight polytetrafluoroethylene powder, 0.4% of metal bismuth powder, and 0.2% of stearic acid are pre-compounded by pin grinding, pulverizing, and dispersing, and then added with 5% of dibutyl ether, 1% of C5 aliphatic petroleum resin, and 0.2% of sorbitan monooleate into a ball mill. The grinding medium of the ball mill is a zirconia ceramic ball with a particle size of 3 mm. The speed is controlled at a low speed of 15 rpm, and the grinding is performed for 30 minutes. Note that the ball mill is operated in a closed manner to prevent volatilization and fire sources; a slurry is obtained by grinding, dissolving, and dispersing under closed conditions;

[0050] S2. According to the mass percentage, 12.5% ​​perfluoropolyether oil, 5% mineral oil, 2.5% silicone oil, 6% barium petroleum sulfonate, 5% tung oil, 2.5% tetrafluoropropanol, 2.5% tridecafluoroheptanoic acid, and 56.2% hydrogenated deodorized kerosene were added to a stirring tank and stirred evenly, and then the slurry ground by S1 was added, stirred evenly at a low speed, filtered, and a rust-proof lubricant was obtained;

[0051] S3. The anti-rust lubricant obtained in step S2 is canned at normal pressure using a tinplate can as a container, the valve is sealed, and a propellant is charged, and the container tank pressure is adjusted to 0.50 MPa; the propellant is LPG and nitrogen in a mass ratio of 3:1, and the amount used is 40% of the total mass of the anti-rust lubricant; after weighing test and water bath test, a nozzle is installed to obtain a self-repairing anti-rust lubricating aerosol.

[0052] In particular, a self-repairing anti-rust lubricating aerosol is obtained for disassembly and installation of the screw rust-bonded meshing block of a twin-screw extruder.

[0053] Example 2

[0054] S1. According to the percentage by mass, 0.5% of graphite, 0.5% of low molecular weight polytetrafluoroethylene powder, 0.4% of metal bismuth powder, and 0.2% of stearic acid are pre-compounded by pin grinding, pulverizing, and dispersing, and then added with 6% of dibutyl ether, 1.5% of C9 aromatic petroleum resin, and 0.2% of sorbitan monooleate into a ball mill. The grinding medium of the ball mill is a zirconia ceramic ball with a particle size of 3 mm. The speed is controlled at a low speed of 15 rpm, and the grinding is performed for 30 minutes. Note that the ball mill is operated in a closed manner to prevent volatilization and fire sources; a slurry is obtained by grinding, dissolving, and dispersing under closed conditions;

[0055] S2. According to the mass percentage, 11% perfluoropolyether oil, 5% mineral oil, 2.5% silicone oil, 8% barium dinonylnaphthalenesulfonate, 6% sulphurized cottonseed oil, 1.5% tetrafluoropropanol, 1.5% tridecafluoroheptanoic acid, 55.2% hydrogenated deodorized kerosene were added to a stirred tank and stirred evenly, and then the slurry ground by S1 was added, stirred evenly at a low speed, filtered, and a rust-proof lubricant was obtained;

[0056] S3. The anti-rust lubricant obtained in step S2 is canned at normal pressure using a tinplate can as a container, the valve is sealed, and a propellant is charged, and the container tank pressure is adjusted to 0.50 MPa; the propellant is LPG and nitrogen in a mass ratio of 4:1, and the amount used is 42% of the total mass of the anti-rust lubricant; after weighing test and water bath test, a nozzle is installed to obtain a self-repairing anti-rust lubricating aerosol.

[0057] Example 3

[0058] S1. According to the percentage by mass, 0.8% of graphite, 0.5% of low molecular weight polytetrafluoroethylene powder, 0.5% of metal bismuth powder, and 0.3% of stearic acid are pre-compounded by air flow pulverization and dispersion, and then added with 5% of dibutyl ether, 1% of alicyclic petroleum resin, and 0.2% of sorbitan monooleate into a ball mill. The grinding medium of the ball mill is a zirconia ceramic ball with a particle size of 3 mm. The speed is controlled at a low speed of 25 rpm, and the grinding is performed for 20 minutes. Note that the ball mill is operated in a closed manner to prevent volatilization and fire sources; a slurry is obtained by grinding, dissolving, and dispersing under closed conditions;

[0059] S2. According to the mass percentage, 12% perfluoropolyether oil, 5% mineral oil, 2.5% silicone oil, 6% dodecenylsuccinic acid, 5% tung oil, 3% tetrafluoropropanol, 2% tridecafluoroheptanoic acid, and 56.2% hydrogenated deodorized kerosene were added to a stirred tank and stirred evenly, and then the slurry ground by S1 was added, stirred evenly at a low speed, filtered, and a rust-proof lubricant was obtained;

[0060] S3. The anti-rust lubricant obtained in step S2 is canned at normal pressure using a tinplate can as a container, the valve is sealed, and a propellant is charged, and the container tank pressure is adjusted to 0.60MPa; the propellant is DME and nitrogen in a mass ratio of 4:1, and the amount used is 45% of the total mass of the anti-rust lubricant; after weighing test and water bath test, a nozzle is installed to obtain a self-repairing anti-rust lubricating aerosol.

[0061] In particular, a self-repairing anti-rust lubricating aerosol is obtained for storage protection of plastic injection molds.

[0062] Example 4

[0063] S1. According to the percentage by mass, 0.5% of graphite, 1% of low molecular weight polytetrafluoroethylene powder, 0.3% of metal bismuth powder, and 0.3% of stearic acid are pre-compounded by air flow pulverization and dispersion, and then added with 6% of dibutyl ether, 1% of alicyclic petroleum resin, and 0.2% of sorbitan monooleate into a ball mill. The grinding medium of the ball mill is a zirconia ceramic ball with a particle size of 3 mm. The speed is controlled at a low speed of 25 rpm, and the grinding is performed for 25 minutes. Note that the ball mill is operated in a closed manner to prevent volatilization and fire sources; a slurry is obtained by grinding, dissolving, and dispersing under closed conditions;

[0064] S2. According to the mass percentage, 12% perfluoropolyether oil, 5% mineral oil, 2.5% silicone oil, 6% dodecenylsuccinic acid, 6% butyl oleate, 2% tetrafluoropropanol, 2% tridecafluoroheptanoic acid, and 55.3% hydrogenated deodorized kerosene were added to a stirred tank and stirred evenly, and then the slurry ground by S1 was added, stirred evenly at a low speed, filtered, and a rust-proof lubricant was obtained;

[0065] S3. The anti-rust lubricant obtained in step S2 is canned at normal pressure using a tinplate can as a container, the valve is sealed, and a propellant is charged, and the container tank pressure is adjusted to 0.60MPa; the propellant is DME and nitrogen in a mass ratio of 4:1, and the amount used is 45% of the total mass of the anti-rust lubricant; after weighing test and water bath test, a nozzle is installed to obtain a self-repairing anti-rust lubricating aerosol.

[0066] The formula of the rust-proof lubricant of Examples 1-4 is shown in Table 1.

[0067] Table 1: Formula of rust-proof lubricant Examples 1-4:

[0068]

[0069] Comparative Example 1

[0070] The aerosol was prepared according to the technical scheme of Example 1, wherein silicone oil was not used in the base oil, but mineral oil was used instead. Compared with the aerosol of Example 1, the uniformity of the oil film after spraying was slightly worse. This is mainly because the use of silicone oil can effectively reduce the surface tension of the base oil and enhance the wetting effect of the base oil on the metal parts.

[0071] Comparative Example 2

[0072] The aerosol was prepared according to the technical scheme of Example 1, wherein tetrafluoropropanol was not used as the penetrant. Compared with the aerosol of Example 1, the aerosol obtained after spraying had a poorer effect on cleaning rust.

[0073] Comparative Example 3

[0074] The aerosol was prepared according to the technical scheme of Example 1, wherein tridecafluoroheptanoic acid was not used as the penetrant. Compared with the aerosol of Example 1, the aerosol obtained after spraying had a poorer effect on cleaning rust. This was mainly because tridecafluoroheptanoic acid had a lower surface tension, which could assist in the wettability and adhesion of the metal surface. Obviously, the penetrant composed of tetrafluoropropanol and tridecafluoroheptanoic acid was missing, and the cleaning effect of the aerosol was significantly worse.

[0075] Comparative Example 4

[0076] According to the technical scheme of Example 1, petroleum resin is not used. The obtained aerosol has a low viscosity after spraying compared with the aerosol of Example 1, and it is difficult to fix the repair agent to form a film for repair. The main reason is that petroleum resin can enhance the adhesion and film-forming property of the aerosol after spraying, thus overcoming the defect that the current lubricant aerosol is difficult to fix and form a film.

[0077] The anti-rust lubricant formulas of Comparative Examples 1-4 are shown in Table 2.

[0078] Table 2: Formula of rust-proof lubricant comparative examples 1-4:

[0079]

[0080] Comparative Example 5

[0081] According to the technical scheme of Example 1, low molecular weight polytetrafluoroethylene was not used, and an equal amount of graphite was used instead. Compared with the aerosol of Example 1, the aerosol obtained was sprayed on the bearing and operated for a period of time. The repair effect of the rust spots of the bearing was weaker than that of Example 1.

[0082] Comparative Example 6

[0083] According to the technical scheme of Example 1, no metal bismuth powder was used, and an equal amount of graphite was used instead. Compared with the aerosol of Example 1, the aerosol was sprayed on the bearing and operated for a period of time. The repair effect of the rust spots of the bearing was significantly weaker than that of Example 1.

[0084] Comparative Example 7

[0085] According to the technical scheme of Example 1, graphite was not used, and an equal amount of polytetrafluoroethylene was used as a slight substitute. Compared with the aerosol of Example 1, the aerosol sprayed on the bearing after running for a period of time had a significantly weaker effect on repairing the rust spots of the bearing than that of Example 1.

[0086] The anti-rust lubricant formulas of Comparative Examples 5-7 are shown in Table 3.

[0087] Table 3 Formula table of rust-proof lubricant comparative examples 5-7:

[0088]

[0089] Anti-rust lubricating aerosol self-repair function test:

[0090] Four groups of aerosols, including Example 1 and Comparative Examples 5-7, were sprayed on the same batch of rusted rolling bearings. After spraying, the bearings were operated for 60 minutes under the same load. The friction surface of the outer ring of the bearings (such as the attached Figure 1A1 is a microscopic magnified image of the spraying aerosol of Example 1; A2 is a microscopic magnified image of the spraying aerosol of Comparative Example 5; A3 is a microscopic magnified image of the spraying aerosol of Comparative Example 6; A4 is a microscopic magnified image of the spraying aerosol of Comparative Example 7. Obviously, Example 1 uses the synergy of graphite, metal bismuth powder, and low molecular weight polytetrafluoroethylene powder. Through metal-metal friction, the repair agent penetrates and embeds in the micro-defects on the defects or tiny rust spots on the metal surface, forming a flat and smooth wear-resistant protective layer, realizing the dynamic repair of the rusted and worn surface metal, and the metal surface repair effect is better than that of Comparative Examples 5-7.

[0091] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the formula and preparation process of the present invention may be subject to various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A self-repairing anti-rust lubricating aerosol, characterized by Comprising a rust-preventing lubricant and a propellant; wherein: The anti-rust lubricant comprises the following raw material components by mass percentage: 18-20% base oil, 5-8% anti-rust agent, 4-6% auxiliary lubricating oil, 3-5% penetrant, 4-6% dibutyl ether, 1-1.5% petroleum resin, 0.5-1% low molecular weight polytetrafluoroethylene powder, 0.5-0.8% graphite, 0.3-0.5% metal bismuth powder, 0.2-0.3% stearic acid, 0.1-0.2% sorbitan monooleate, and the rest is hydrogenated deodorized kerosene; The amount of the propellant is 40-45% of the total mass of the anti-rust lubricant; The base oil is a mixture of perfluoropolyether oil, mineral oil and silicone oil in a mass ratio of 3-5:2:1; The rust inhibitor is at least one of barium petroleum sulfonate, calcium petroleum sulfonate, sodium petroleum sulfonate, barium dinonylnaphthalene sulfonate, calcium dinonylnaphthalene sulfonate, 2,6-di-tert-butyl-p-cresol (BHT), and dodecenylsuccinic acid; The auxiliary lubricating oil is one of tung oil, sulphurized cottonseed oil and butyl oleate; The penetrant is prepared by mixing tetrafluoropropanol and tridecafluoroheptanoic acid in a mass ratio of 1-2:1; The petroleum resin is at least one of C5 aliphatic petroleum resin, C9 aromatic petroleum resin, C5-C9 aliphatic / aromatic copolymer petroleum resin, and alicyclic petroleum resin; The propellant is a complex of at least one of liquefied petroleum gas, dimethyl ether and carbon dioxide and nitrogen.

2. The self-repairing anti-rust lubricating aerosol according to claim 1, characterized in that: The base oil is prepared by blending perfluoropolyether oil, mineral oil and silicone oil in a mass ratio of 4:2:

1.

3. The self-repairing anti-rust lubricating aerosol according to claim 1, characterized in that: The penetrant is prepared by blending tetrafluoropropanol and tridecafluoroheptanoic acid in a mass ratio of 1:

1.

4. The self-repairing anti-rust lubricating aerosol according to claim 1, characterized in that: The low molecular weight polytetrafluoroethylene micropowder is a low molecular weight polytetrafluoroethylene micropowder with a number average molecular weight (Mn) of 10,000 to 30,000 and a D50 particle size of less than 5 μm.

5. The self-repairing anti-rust lubricating aerosol according to claim 1, characterized in that: The graphite particle size is less than 5 μm of flake graphite.

6. The self-repairing anti-rust lubricating aerosol according to claim 1, characterized in that: The metal bismuth powder is bismuth powder with a particle size less than 2 μm.

7. The self-repairing anti-rust lubricating aerosol according to claim 1, characterized in that: The propellant is a complex of at least one of liquefied petroleum gas, dimethyl ether and carbon dioxide and nitrogen in a mass ratio of 3-5:

1.

8. A method for preparing a self-repairing anti-rust lubricating aerosol according to any one of claims 1 to 7, characterized in that: The specific preparation method is as follows: S1. According to the mass percentage, graphite, low molecular weight polytetrafluoroethylene powder, metal bismuth powder, and stearic acid are pre-compounded by mechanical grinding and dispersion, and then added to a ball mill with dibutyl ether, petroleum resin, and sorbitan monooleate, and closed grinding, dissolving, and dispersing under ceramic grinding ball conditions to obtain a slurry; S2 according to the mass percentage ratio of the base oil, rust inhibitor, auxiliary lubricant, penetrant, hydrodeodorized kerosene added to the stirred tank and stirred evenly, then added S1 grinded slurry, stirred at low speed, filtered to obtain a rust-proof lubricant; S3. The anti-rust lubricant obtained in step S2 is canned at normal pressure using a tinplate can as a container, the valve is sealed, a propellant is charged, the weighing test and the water bath test are performed, and a nozzle is installed to obtain a self-repairing anti-rust lubricating aerosol.

9. The method for preparing a self-repairing anti-rust lubricating aerosol according to claim 8, characterized in that: In step S1, the ball mill is controlled at a low speed of 15-25 rpm and grinds for 20-30 minutes; the particle size of the ceramic grinding balls is 3 mm.

10. The method for preparing a self-repairing anti-rust lubricating aerosol according to claim 8, characterized in that: In step S1, the graphite, low molecular weight polytetrafluoroethylene powder, metal bismuth powder and stearic acid are pre-compounded by mechanical grinding, pulverizing and dispersing, using methods including but not limited to: air flow pulverizing, pin grinding pulverizing, vortex air flow pulverizing and impact grinding pulverizing.